A tale of two cities - Dickens , Charles (UK Puffin Classics, 2009)
A Tale of Two Cities by Charles Dickens is set during the turbulent time of the French Revolution and focuses on the themes of resurrection, sacrifice, and social injustice. The novel contrasts two cities$1 (BLondon and Paris$1 (Band their experiences during the Revolution. The story follows several key characters: Charles Darnay: A French aristocrat who renounces his title and moves to England to live a life of humility. Sydney Carton: A talented but disillusioned English lawyer who struggles with his wasted potential and lack of purpose. Lucie Manette: The loving and compassionate daughter of Dr. Alexandre Manette, who is reunited with her father after being imprisoned in the Bastille for eighteen years. Dr. Manette: A brilliant doctor who has been psychologically scarred by his long imprisonment and is deeply devoted to his daughter.s
Keywords: English Novel Book; English fiction book